Association of tumour burden with the efficacy of programmed cell death-1/programmed cell death ligand-1 inhibitors for treatment-naïve advanced non-small-cell lung cancer. (January 2022) - Suzuki, Shinichiro; Haratani, Koji; Hayashi, Hidetoshi; Chiba, Yasutaka; Tanizaki, Junko; Kato, Ryoji; Mitani, Seiichiro; Kawanaka, Yusuke; Kurosaki, Takashi; Hasegawa, Yoshikazu; Okabe, Takafumi; Tanaka, Kaoru; et al.
Abstract: Background: Tumour burden (TB) is implicated in resistance to programmed cell death-1/PD-L1 inhibitor (immune checkpoint inhibitor [ICI]) therapy. However, whether TB contributes to such resistance in non-small-cell lung cancer (NSCLC) has remained unknown. Methods: A total of 260 treatment-naïve patients with advanced NSCLC who started ICI monotherapy (ICI cohort), platinum-doublet therapy (Chemo cohort) or ICI and platinum-doublet therapy (ICI+Chemo cohort) as first-line treatment were consecutively included. TB was estimated on the basis of the sum of the diameters of measurable target lesions as per Response Evaluation Criteria in Solid Tumours. Progression-free survival (PFS) in the ICI cohort was evaluated as per TB as a preplanned primary objective, with the analysis based on propensity score-weighted survival curves and estimation of restricted mean survival time (RMST). The Chemo cohort served as a control to determine whether TB is predictive of ICI treatment outcomes. The ICI+Chemo cohort was exploratory. The relation of TB to tumour immune status was assessed by immune-related gene expression profiling (irGEP) of pretreatment tumour tissue. Results: In the ICI cohort, patients with a low TB showed a significantly longer PFS than did those with a high TB (median, 17.9 vs 4.3 months; weighted hazard ratio, 0.32 [95% confidence interval, 0.19–0.53]). No such difference was apparent in the other cohorts. A significant difference in overall survival was also observed only in the ICI cohort. RMST-based analysis confirmed these results. The irGEP analysis implicated M2-type macrophages, angiogenesis and transforming growth factor–β as well as protumourigenic signalling pathways in ICI resistance conferred by a high TB. Conclusion: A high TB was associated with a poor outcome of ICI therapy for advanced NSCLC as a result of immunosuppressive phenotypes. Development of combination or novel treatment strategies for such disease is thus warranted. Highlights: The relation of NSCLC tumour burden to PD-1/PD-L1 inhibitor efficacy was evaluated. High tumour burden (HTB) was associated with resistance to ICI monotherapy. HTB was not associated with treatment outcomes for cytotoxic chemotherapy. HTB was associated with macrophage-related and protumourigenic gene expression. Patients with HTB may require more aggressive treatment than ICI monotherapy.